MODELING OF INFORMATIONAL AND PSYCHOLOGICAL IMPACT ON SOCIETY - Artemov, Volodymyr; Khoroshko, Volodymyr; Khokhlachova, Yuliia (Ukrainian Information Security Research Journal, 2023)
The article provides a definition of informational and psychological influences (IPV) and the main scales of their influence on social groups of society. A description of the model leading to the form of a nonlinear differential equation is given. The model considers the informational impact on the mass consciousness of interpersonal informational interaction, mass media and the effect of forgetting the impact of IPV. It is shown that the model has a solution in the form of a generalized logistic curve. The statistical distribution over time of individual members of society who support the ideas of IPV is given, which qualitatively confirms the formal solution of the model. Individual cases of the model were studied, which in all cases confirm the existence of an asymptotic stationary solution. It is emphasized that the development of the model is observed in the conditions of hybrid war and ensuring the information security of the state, society and each individual member of society, requiring and considering the development of social networks.